HIGH-DURABLE TECHNOLOGICAL AUXILIARIES FOR ROLLING MILLS OF RUP “BMZ - S. S. Gurin; D. M. Kukuj; N. V. Andrianov (Литьë и металлургия, 2005)
The developments of highly abrasion-resistant material with bulk properties, able to work in condition of intense heat-changing are given. The results of the work are implemented at the mill 320/150 RUP ‘"BMZ”.